Usable Live Programming (web essay) - McDirmid, Sean (2013)
Programming today involves editing code while simulating how that code will run in our head to ensure that program goals are met. To augment this mental simulation, editing is periodically interrupted by bouts of debugging to get feedback on how code really executes. Live programming promises for much more fluid feedback between the programmer and a program that is executing while it is being edited.